Implementasi Kompetensi Personal Pustakawan dalam Konsep 4B (Beauty, Brain, Behaviour, Brave) di Perpustakaan Daerah Kabupaten Tulungagung - Firulla Quthbi Habibin; Maydani Nur Majidah (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This study aims to examine the implementation of librarians' personal competencies within the framework of the 4B concept (Beauty, Brain, Behaviour, Brave) at the Regional Library of Tulungagung Regency. The 4B concept was initially popularized in the pageant world but has since evolved into an approach applicable to service-oriented professions, including librarianship. This research employs a descriptive qualitative approach, using in-depth interviews with three informants: the Head of the Library and Archives Service and two female librarians who also serve as division heads. The findings indicate that each element of the 4B concept is evidently manifested in the personal competencies of female librarians. The beauty aspect reflects not only physical appearance but also personal integrity and efforts to create an appealing service environment. Brain is demonstrated through mastery of knowledge and librarianship skills. Behaviour is reflected in professional attitudes, empathy, and work ethics in service interactions. Meanwhile, brave is embodied in the courage of female librarians to take on strategic roles, lead innovations, and face challenges in the public sphere. These findings reinforce the perspective that female librarians possess capabilities equal to their male counterparts in terms of professionalism and play an active role in challenging gender stereotypes in the library environment. This research contributes to the development of a humanistic and gender-equality-based librarian competency model.